The factors that influence employee’s overall health at Lembaga Zakat Negeri Kedah / Nur Izafini Abdul Muttalib - Muttalib, Nur Izafini Abdul
Past study has consistently reported empirical evidence of higher job stress and poorer mental health among employees. Although employees experience higher job stress, poorer mental health and different job stress dimensions, little is known about which factors that influence employee’s overall health. Therefore, this study investigated the factors that influence overall health of employees in Lembaga Zakat Negeri Kedah (LZNK). Data for the study were collected from 112 employees. This research found autonomy to be one of the predictors of employee’s overall health along with relationship, reward and mental health.